2014
DOI: 10.5114/aoms.2014.44865
|View full text |Cite
|
Sign up to set email alerts
|

Relation between abdominal subcutaneous fat tissue thickness and inflammatory markers during pregnancy

Abstract: IntroductionSubcutaneous abdominal fat thickness (SCFT) is important for predisposition to metabolic and cardiovascular diseases. Our aim was to evaluate maternal SCFT and metabolic changes (such as insulin resistance and high inflammatory markers) during pregnancy.Material and methodsA total of 92 pregnant women between 24–28 weeks of gestation were enrolled in the study. The SCFT was measured by ultrasonography and patients were divided into 2 groups according to thickness of maternal SCFT and body mass inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
2
15
0
3
Order By: Relevance
“…Data from the Framingham Heart Study demonstrated that both visceral and subcutaneous fat volume are associated with an increased risk of metabolic syndrome, with visceral fat showing a stronger relation . Greater maternal abdominal subcutaneous fat thickness has been shown to correlate with higher serum levels of hemoglobin A1C and C reactive protein in pregnant women . Recently, the utility of maternal abdominal subcutaneous fat thickness (SCFT) as a measure of abdominal obesity in pregnancy and as a predictor of pregnancy outcomes has been explored .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the Framingham Heart Study demonstrated that both visceral and subcutaneous fat volume are associated with an increased risk of metabolic syndrome, with visceral fat showing a stronger relation . Greater maternal abdominal subcutaneous fat thickness has been shown to correlate with higher serum levels of hemoglobin A1C and C reactive protein in pregnant women . Recently, the utility of maternal abdominal subcutaneous fat thickness (SCFT) as a measure of abdominal obesity in pregnancy and as a predictor of pregnancy outcomes has been explored .…”
Section: Introductionmentioning
confidence: 99%
“…6 Greater maternal abdominal subcutaneous fat thickness has been shown to correlate with higher serum levels of hemoglobin A1C and C reactive protein in pregnant women. 7 Recently, the utility of maternal abdominal subcutaneous fat thickness (SCFT) as a measure of abdominal obesity in pregnancy and as a predictor of pregnancy outcomes has been explored. 8,9 Suresh et al 8 retrospectively studied 1200 nulliparous women and found an ultrasound measurement of abdominal SCFT was better than BMI at predicting gestational diabetes, cesarean delivery and large-for-gestational-age neonates.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, the authors concluded that EAT acts as an extremely active organ that produces several bioactive adipokines, as well as proinflammatory and proatherogenic cytokines including tumor necrosis factor (TNF)-α, interleukin (IL)-6, resistin, visfatin, omentin, leptin, plasminogen activator inhibitor-1 (PAI-1) and angiotensinogen [15, 1821]. In addition, abdominal subcutaneous fat tissue was also found to be closely associated with inflammation in physiologic conditions such as pregnancy [22]. …”
Section: Introductionmentioning
confidence: 99%
“…This finding is clinically significant as higher inflammation might contribute to the increased acute and chronic risk for the development of metabolic complications (e.g. insulin resistance, gestational diabetes, hypertension, metabolic syndrome, cardiovascular disease) (Catalano et al 2009a; Kosus et al 2014; Ozgu-Erdinc et al 2014) as well as additional risks for maternal infection, preterm delivery, and severe preeclampsia (Schmatz et al 2010). Additionally, higher inflammation in inactive obese women during pregnancy will likely persist into postpartum (Christian and Porter 2014); thus, potentially contributing to a higher long-term diabetes and cardiovascular disease risk (Lagrand et al 1999).…”
Section: Discussionmentioning
confidence: 99%